2018
DOI: 10.1002/tafs.10067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aquatic Macrophytes on Age‐0 Largemouth Bass Growth and Diets

Abstract: Macrophyte removal by lakefront property owners occurs on glacial lakes throughout the range of Largemouth Bass Micropterus salmoides, yet little information exists on how it affects recruitment of these fish populations. We hypothesized that with greater prey availability in macrophytes, age‐0 Largemouth Bass consumption and growth would increase. To test this hypothesis, we conducted an in‐lake experiment with age‐0 Largemouth Bass in twelve 9.29‐m2 littoral mesocosms in glacial Chancellor Lake, Michigan, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…At lake scale, considering the whole water body, studies usually investigate the general patterns of fish–macrophyte relationship such as fish abundance, composition, distribution and reproduction (Cheruvelil et al, 2005; Maceina et al, 1991). At point scale, considering the macrophyte patch that the fishes actually exploit (Dibble et al, 1996), studies have addressed the behavioural ecology of fishes and the process by which they interact with the plants, providing insight into how macrophytes affect fish foraging, diets and behavioural responses (Carniatto et al, 2020; Miranda & Hodges, 2000; Nohner et al, 2018; Padial et al, 2009; Savino & Stein, 1982). In addition, the unimodal relationship between macrophyte cover and fish attributes (e.g., fish abundance and richness), usually observed at microscale (Cunha et al, 2019; Quirino, Lansac‐Tôha, et al, 2021), may not be detected at whole‐lake scale.…”
Section: Introductionmentioning
confidence: 99%
“…At lake scale, considering the whole water body, studies usually investigate the general patterns of fish–macrophyte relationship such as fish abundance, composition, distribution and reproduction (Cheruvelil et al, 2005; Maceina et al, 1991). At point scale, considering the macrophyte patch that the fishes actually exploit (Dibble et al, 1996), studies have addressed the behavioural ecology of fishes and the process by which they interact with the plants, providing insight into how macrophytes affect fish foraging, diets and behavioural responses (Carniatto et al, 2020; Miranda & Hodges, 2000; Nohner et al, 2018; Padial et al, 2009; Savino & Stein, 1982). In addition, the unimodal relationship between macrophyte cover and fish attributes (e.g., fish abundance and richness), usually observed at microscale (Cunha et al, 2019; Quirino, Lansac‐Tôha, et al, 2021), may not be detected at whole‐lake scale.…”
Section: Introductionmentioning
confidence: 99%
“…The littoral zone of a lake can be viewed as a complex landscape, comprised of distinct habitats that provide varying resources and refuge for fish and other fauna (Chick and McIvor 1994). Within a littoral zone, the complex habitat created by submerged aquatic vegetation (SAV) can provide ecological benefits that result in an increase in abundance, biomass, and species diversity of fish and other fauna (Thorp et al 1997; Richardson et al 1998; Nohner et al 2018). For example, young Largemouth Bass Micropterus salmoides feed mostly on zooplankton, macroinvertebrates, and small fish (Keast and Eadie 1985; Carpenter et al 1987; Miner and Stein 1993; Middaugh et al 2013), and these organisms tend to be most abundant in vegetated areas (Moxley and Langford 1982; Warren and Vogel 1991; Beckett et al 1992; Spoljar et al 2012; Middaugh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Texas reservoirs, the standing stock and recruitment of Largemouth Bass declined when SAV cover was less than 20% (Durocher et al 1984). In Michigan, a 60% cover of littoral habitat was recommended to decrease mortality and improve recruitment of age‐0 Largemouth Bass (Nohner et al 2018), and in central Florida lakes the abundance and survival of age‐0 Largemouth Bass were positively correlated with the percent cover of hydrilla Hydrilla verticillata when coverages were as high as 75% and 91% (Tate et al 2003). Although Largemouth Bass selectively use SAV habitat, the growth and condition of adult Largemouth Bass may decrease when the coverage of aquatic macrophytes is extremely high (Colle and Shireman 1980, Engle 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In glacial lakes, local densities of YOY largemouth bass are related to local habitat features such as vegetation coverage (Middaugh et al, 2013). Moreover, habitat characteristics have been shown to lead to differences in growth rates of YOY largemouth bass, with increased growth in edge or vegetated habitats (Nohner et al, 2018). However, past studies mainly focus on short‐term habitat use, and it is unknown if observed short‐term preferences translate to long‐term individual habitat use.…”
Section: Introductionmentioning
confidence: 99%
“…In glacial lakes, local densities of YOY largemouth bass are related to local habitat features such as vegetation coverage (Middaugh et al, 2013). Moreover, habitat characteristics have been shown to lead to differences in growth rates of YOY largemouth bass, with increased growth in edge or vegetated habitats (Nohner et al, 2018).…”
mentioning
confidence: 99%